Analisis Kepatuhan Pajak pada Pelaku UMKM di Tinjau dari Sistem dan Pelayanan Pajak - Dwi Fionasari; Armina Khoiriyah Nasution; Rezeki Putri Utami; Zahwa Aulia; Fakhrul Ilham; Muhammad Hanif Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy through their contribution to employment and national economic growth. However, tax compliance among MSME taxpayers remains relatively low due to limited understanding of tax regulations and administrative procedures. This study aims to analyze tax compliance among MSME actors in Binawidya District, Pekanbaru, from the perspectives of the tax system and tax services. A qualitative research method with a descriptive interpretive approach was employed. Data were collected through observation, semi-structured interviews, documentation, and literature review involving five food-sector MSMEs selected using purposive sampling. The data were analyzed using the Miles and Huberman interactive analysis model, including data reduction, data display, and conclusion drawing. The findings indicate that MSME owners generally recognize the importance of financial records and taxation for business sustainability. However, their understanding remains limited to simple bookkeeping and has not yet developed into structured financial reporting. Tax compliance is influenced not only by taxpayers' awareness but also by the accessibility of tax services, administrative simplicity, and digital tax systems. Although Government Regulation Number 20 of 2026 introduces changes to MSME taxation, the studied respondents are generally unaffected because they operate as individual businesses. The study implies that improving financial literacy, tax education, and accessible tax services is essential to strengthen voluntary tax compliance among MSMEs.